Factors Associated with Job Stress among Ambulance Nurses in Bangkok - Sakkomonsri, Jutamanee; Suwan-Ampai, Plernpit; Kaewboonchoo, Orawan (The Bangkok Medical Journal, 2016)
OBJECTIVE: to explore the factors associated with job stress among the ambulancenurses in nine zones of Bangkok Emergency Medical Service (EMS). MATERIALS AND METHODS: Multistage random sampling was conductedbetween December 2015 and February 2016. Two hundred and forty-five ambulancenurses of network hospitals in nine zones of Bangkok EMS who had at least 40hours EMS training and at least six months work experiences on ambulance wereselected as study samples. A self-administered questionnaire with specific questionsto explore variables such as socio-demographics, work characteristics, generalwell-being, employee engagement, role and social support was used. Job stress wasevaluated using the Karasek’s Job Demand-Control model (JCQ). The predictivefactors influencing job stress were analyzed by using Chi-square and multiplelogistic regressions. RESULTS: A total of 245 ambulance nurses were enrolled in the study. One third(33.5%) of ambulance nurses developed high work stress. A statistically significantassociation was observed between job stress and older age (OR = 0.94, 95% CI:0.89 - 0.99), higher incomes (OR = 0.26, 95% CI: 0.09 - 0.69), higher educationlevel (OR = 4.17, 95% CI: 1.13 - 15.47), more work experience (OR = 0.32, 95%CI: 0.12 - 0.88), perception of urgent task (OR = 8.00, 95% CI: 1.44 - 44.73), poorgeneral well-being (OR = 2.36, 95% CI : 1.00 - 5.55), low superior support (OR =12.50, 95% CI: 4.62 - 33.78), low peer support (OR = 3.27, 95% CI: 1.30 - 8.21),role ambiguity (OR = 12.45, 95% CI: 4.77 - 32.51), and role conflict (OR = 14.48,95% CI: 5.14 - 40.82). CONCLUSION: The executive and nursing administrators should be aware of jobstrain among ambulance nurses particularly in the younger age group with less than5 years of working experience. Specific training programs with supervision and peersupport should be provided. Stress management should be commenced in nursingeducation. The clarity of role and duty together with appropriate work schedule shouldbe considered to avoid the stressful situation which in turn will reduce job stress. Thisstudy is the first investigation that quantifies the strength of association between jobstress and the various factors among ambulance nurses, thereby enabling themanagement to implement logical and preventive strategies regarding work-relatedstress and improve the quality of care in the future.